"I Will Not Keep Her Book in My Home": Representing Religious Meaning among Bauls. Issue 1 (1st March 2016) - Knight, Lisa I.
Abstract : Anthropologists have long been concerned with issues of representation and the problematic structures of power that characterize the relationship of researcher and subject. This article takes field work confrontations and anxieties as opportunities through which to examine some of the challenges of representing religious lives in comprehensible and meaningful ways, not simply to scholars but also—perhaps especially—to those from within the tradition we're studying. Drawing on work that emphasizes dialogical processes of knowledge production and its ethical implications, the author considers moments of transformation during and resulting from fieldwork as a model for moving forward.